Can investments in social protection contribute to subjective well-being? A cross-country analysis - Kolev, Alexandre (OECD Publishing, 2016)
Subjective well-being has in recent years been recognised as a goal of development that captures non-monetary or subjective dimensions of well-being. The body of evidence on the individual and societal determinants of subjective well-being is growing, but the literature remains in its infancy as to the role of social protection despite important policy implications. The objective of this paper is to explore the relationship between investments in social protection (as a proxy for the level of social protection services received by the population) and individuals' evaluative and experienced well-being. This paper thus provides new evidence on the relationship between social protection investments and subjective well-being based on a worldwide sample including 38 countries and covering low-, middle- and high-income countries. Furthermore, we study potential channels explaining this relationship by considering the effect on potential beneficiaries and non-beneficiaries as well as distributional effects
Keywords: Development